2016
DOI: 10.1098/rspb.2016.1211
|View full text |Cite
|
Sign up to set email alerts
|

Optimal frequency of rabies vaccination campaigns in Sub-Saharan Africa

Abstract: Rabies causes more than 24 000 human deaths annually in Sub-Saharan Africa. The World Health Organization recommends annual canine vaccination campaigns with at least 70% coverage to control the disease. While previous studies have considered optimal coverage of animal rabies vaccination, variation in the frequency of vaccination campaigns has not been explored. To evaluate the cost-effectiveness of rabies canine vaccination campaigns at varying coverage and frequency, we parametrized a rabies virus transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…Studies in sub-Saharan Africa countries, where rabies is a public health concern, have shown that investments made to vaccinate a sufficient proportion of dogs would likely minimize the health burden and expenditures related to PET [ 50 ; 51 ; 52 ]. Strategies to reduce human rabies in Ethiopia should, therefore, include mass dog vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in sub-Saharan Africa countries, where rabies is a public health concern, have shown that investments made to vaccinate a sufficient proportion of dogs would likely minimize the health burden and expenditures related to PET [ 50 ; 51 ; 52 ]. Strategies to reduce human rabies in Ethiopia should, therefore, include mass dog vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…V-S interventions are likely to be conducted on relatively small spatial scales due to longer implementation time, and expanding them geographically is likely to be challenging [59]. Geographical co-ordination is key as reintroduction of rabies from non-vaccinated areas is a challenge in rabies control [60].…”
Section: Role Of Sterilisationmentioning
confidence: 99%
“…This cost-effectiveness analysis is the first study to include cattle rabies-related losses, a component which has particular importance for livestock-dependent communities. Previous canine vaccination evaluations in Africa and elsewhere have focused primarily on the prevention of human rabies [6,19,[44], [45], [46], [47], [48]]. These studies indicated that high canine vaccination coverage would be cost-effective on the basis of the human health burden alone.…”
Section: Discussionmentioning
confidence: 99%